Perceived Risks Contra Benefits of Using Biosimilar Drugs in Ulcerative Colitis: Discrete Choice Experiment among Gastroenterologists - Baji, Petra; Gulácsi, László; Golovics, Petra A; Lovász, Barbara D; Péntek, Márta; Brodszky, Valentin; Rencz, Fanni; Lakatos, Péter L (Value in health regional issues, 2016)
BACKGROUND: In middle-income countries, access to biological therapy is limited in ulcerative colitis in terms of the number of patients and the length of therapy. Because of their cost advantages, biosimilars have the potential to improve access to therapy, but physicians have concerns toward their use because of the lack of evidence from randomized clinical trials. OBJECTIVES: To explore the preferences of gastroenterologists for biosimilar drugs in ulcerative colitis as well as to compare our results with results of previous studies on gastroenterologists' preferences toward biosimilars. METHODS: A discrete choice experiment was carried out involving 51 Hungarian gastroenterologists treating patients with inflammatory bowel disease in May 2014 with the following attributes: type of treatment (biosimilar/originator), severity of disease, availability of continuous medicine supply, and the stopping rule (whether the treatment is covered after 12 months). A conditional logit model was used to estimate the probabilities of choosing a given profile. RESULTS: According to the results, the stopping rule was the most important attribute. The type of treatment mattered only for patients already on biologicals. The probabilities of choosing the biosimilar option with all the benefits offered in the discrete choice experiment over the originator option under the present reimbursement conditions are 85% for new patients and 63% for patients already treated. CONCLUSIONS: Most gastroenterologists have concerns about using biosimilars. They, however, are willing to consider the use of biosimilars if they could reallocate the potential savings to provide their patients better access to biological treatment.
Keywords: Infliximab; infliximab; lékařská praxe - způsoby provádění; gastroenterologové; Biosimilar Pharmaceuticals; Antibodies, Monoclonal; Inflammatory Bowel Diseases; lidé; Colitis, Ulcerative; biosimilární léčivé přípravky; gastrointestinální látky; Crohn Disease; Gastroenterologists; ulcerózní kolitida; Hungary; idiopatické střevní záněty; monoklonální protilátky; Crohnova nemoc; Gastrointestinal Agents; Maďarsko; Practice Patterns, Physicians'; Humans